The Effect of Adding Variations in the Combination of Anthocyanin Extract and Curcumin Volume Fraction on the Mechanical Properties and Biodegradability of Seaweed-Based Bioplastic Materials - Nuzulul Rahmah; Sujito; Yuda Cahyoargo Hariadi (Jurnal Penelitian Pendidikan IPA, 2025)
The environmental issues caused by conventional plastic waste are becoming increasingly serious, driving the development of more eco-friendly bioplastics. This study examines the mechanical properties, solubility, and biodegradability of seaweed-based bioplastics with the addition of curcumin and anthocyanin as additives. The results indicate that bioplastics containing only anthocyanin exhibit the best tensile strength (3.78 ± 0.26 MPa) and elasticity (12.48 ± 0.49 MPa). In contrast, bioplastics containing only curcumin show the lowest mechanical properties. The addition of anthocyanin enhances tensile strength and elasticity through the formation of strong hydrogen bonds with seaweed polymers, whereas curcumin decreases mechanical properties due to less stable molecular interactions. In terms of solubility, anthocyanin recorded the highest value (72.04%), while curcumin had the lowest (37.61%) due to its lower water stability. Regarding biodegradability, the combination of anthocyanin (1.25%) and curcumin (3.75%), as well as pure curcumin (5%), showed the highest degradation rates, whereas a balanced mixture (2.5%:2.5%) exhibited the lowest biodegradability. In conclusion, anthocyanin improves the mechanical properties and solubility of bioplastics, while curcumin supports biodegradability. Seaweed-based bioplastics with added curcumin and anthocyanin show potential as eco-friendly antibacterial materials.